An active cooling system for photovoltaic module - Teo, H. G.; Lee, P. S.; Hawlader, Mohammad Nurul Alam (Elsevier, 2012)
The electrical efficiency of photovoltaic (PV) cell is adversely affected by the significant increase of cell operating temperature during absorption of solar radiation. A hybrid photovoltaic/thermal (PV/T) solar system was designed, fabricated and experimentally investigated in this work. To actively cool the PV cells, a parallel array of ducts with inlet/outlet manifold designed for uniform airflow distribution was attached to the back of the PV panel. Experiments were performed with and without active cooling. A linear trend between the efficiency and temperature was found. Without active cooling, the temperature of the module was high and solar cells can only achieve an efficiency of 8–9%. However, when the module was operated under active cooling condition, the temperature dropped significantly leading to an increase in efficiency of solar cells to between 12% and 14%. A heat transfer simulation model was developed to compare to the actual temperature profile of PV module and good agreement between the simulation and experimental results is obtained.